Correction: Chemical fingerprinting and quantitative monitoring of the doping drugs bambuterol and terbutaline in human urine samples using ATR-FTIR coupled with a PLSR chemometric tool. Issue 16 (4th March 2020) - Algethami, Faisal K.; Eid, Sherif M.; Kelani, Khadiga M.; Elghobashy, Mohamed R.; Abd El-Rahman, Mohamed K.
Abstract : Correction for 'Chemical fingerprinting and quantitative monitoring of the doping drugs bambuterol and terbutaline in human urine samples using ATR-FTIR coupled with a PLSR chemometric tool' by Faisal K. Algethami et al., RSC Adv., 2020, 10, 7146–7154.